دوافع استخدام مواقع التواصل الاجتماعي في التجارة الالكترونية - توفيق زغب; محمد فتحي تجيني (جامعة الوادي - University of Eloued, 2025)
" من خلال دراستنا هذه تناولنا موضوع * دوافع إستخدام مواقع التواصل الاجتماعي في التجارة الالكترونية * لمعالجة هذه الدراسة قمنا بدراسة ميدانية على عينة من قسم علوم الإعلام والاتصال بجامعة الوادي، وللتحقق من إشكالية دراستنا اعتمدنا على المنهج الوصفي التحليلي ووظفنا أدوات لجمع البيانات تمثلت في الملاحظة العلمية و استمارة الاستبيان والتي طبقت على عينة من طلبة ماستر علوم الإعلام والاتصال حيث تم تقسيم الاستمارة إلى ثلاث محاور: - مواقع التواصل الاجتماعي وفق نظرية الاستخدامات والإشباعات - التجارة الالكترونية وفق نظرية الإستخدمات والاشباعات - العلاقة بين مواقع التواصل الاجتماعي والتجارة الالكترونية وفق نظرية الاستخدامات والاشباعات توصلت الدراسة الى نتائج أهمها : - الطلبة ينجذبون بدرجة كبيرة إلى هذه المنصات بدافع التواصل الاجتماعي والتعبير عن الذات، كما تحقق لهم هذه المواقع مجموعة من الإشباعات النفسية والمعرفية والاجتماعية، أبرزها الشعور بالانتماء، وتطوير المهارات، والرضا عند التفاعل مع الآخرين. - دوافع الطلبة تتجه نحو الفوائد العملية التي توفرها التجارة الالكترونية ،كسهولة الوصول إلى المنتجات، العروض والتخفيضات، وتوفير الوقت والجهد. وفي المقابل، ورغم الإشباعات التي توفرها، مثل تلبية الاحتياجات والتوفير المالي،برزت بعض المخاوف خاصة في ما يتعلق بالأمان الإلكتروني وجودة المنتجات. - الطلبة يوظفون وسائل التواصل الاجتماعي كمنصة للتسوق الالكتروني،حيث تمثل مصدر مهم للمعلومات والعروض، وتُسهم في تعزيز ثقتهم بالعلامات التجارية وتحقيق متعة وتفاعلية أكبر في تجربتهم التسويقية. بناءًا على ما سبق،يمكن القول إن مواقع التواصل الاجتماعي والتجارة الإلكترونية تمثلان فضاءًا مشتركًا متعدد الوظائف،يحقق للطلبة توازنًا بين الإشباع المعرفي،والاجتماعي، والاستهلاكي،ويعكس تطور سلوكيات الاستخدام الرقمي لدى الطالب الجامعي في ظل التحولات الرقمية المتسارعة" "This study addresses the topic: ""Motivations for Using Social Media in E-Commerce."" To investigate this topic, a field study was conducted on a sample from the Department of Media and Communication Sciences at the University of El Oued. In order to explore the research problem, the descriptive-analytical method was adopted. Data collection tools included scientific observation and a questionnaire distributed to Master's students in Media and Communication Sciences. The questionnaire was structured around three main axes: Social media according to the Uses and Gratifications Theory E-commerce in light of the Uses and Gratifications Theory The relationship between social media and e-commerce within the framework of the Uses and Gratifications Theory The study reached several key findings: Students are strongly drawn to social media platforms primarily for social interaction and self-expression. These platforms provide various psychological, cognitive, and social gratificationsmost notably, a sense of belonging, skill development, and satisfaction through interaction with others. Students motivations are directed toward the practical benefits offered by e-commerce, such as easy access to products, discounts and promotions, and saving time and effort. However, despite the gratifications providedsuch as meeting needs and financial savingssome concerns were raised, particularly regarding cybersecurity and product quality. Students use social media as a platform for online shopping, considering it a significant source of information and promotional content. It also helps build their trust in brands and enhances the enjoyment and interactivity of their shopping experience. Based on these findings, it can be concluded that social media and e-commerce constitute a multifunctional shared space that provides students with a balanced mix of cognitive, social, and consumer gratifications. This reflects the evolving digital behavior of university students amid rapid digital transformations.
مذكرة ماستر قسم اعلام واتصال تخصص سمعي بصري
Keywords: مواقع التواصل الاجتماعي; التجارة الالكترونية; Social Media; E-Comme